2016
DOI: 10.1097/aud.0000000000000327
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Hearing Aid Technology on Outcomes in Daily Life II: Speech Understanding and Listening Effort

Abstract: Objectives Modern hearing aid (HA) devices include a collection of acoustic signal-processing features designed to improve listening outcomes in a variety of daily auditory environments. Manufacturers market these features at successive levels of technological sophistication. The features included in costlier premium hearing devices are designed to result in further improvements to daily listening outcomes compared to the features included in basic hearing devices. However, independent research has not substan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 35 publications
3
37
1
1
Order By: Relevance
“…It should be noted, however, that we have failed previously to observe significant differences in hearing aid outcomes, for outcome measures similar to those in this study, for a wide range of hearing-aid technologies, including some that today would be representative of simpler OTC devices ( Humes, Ahlstrom, Bratt, & Peek, 2009 ). More recently, Cox and colleagues have demonstrated equivalent outcomes between basic and advanced contemporary hearing aids ( Cox, Johnson, & Xu, 2014 , 2016 ; Johnson, Xu, & Cox, 2016 ). Nonetheless, the results from this study using high-quality hearing aids cannot be generalized to other devices, including those more likely to be used in OTC approaches to hearing aid delivery.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted, however, that we have failed previously to observe significant differences in hearing aid outcomes, for outcome measures similar to those in this study, for a wide range of hearing-aid technologies, including some that today would be representative of simpler OTC devices ( Humes, Ahlstrom, Bratt, & Peek, 2009 ). More recently, Cox and colleagues have demonstrated equivalent outcomes between basic and advanced contemporary hearing aids ( Cox, Johnson, & Xu, 2014 , 2016 ; Johnson, Xu, & Cox, 2016 ). Nonetheless, the results from this study using high-quality hearing aids cannot be generalized to other devices, including those more likely to be used in OTC approaches to hearing aid delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Participants reported that the perceived sound quality for made-for-smartphone hearing aids was superior in comparison with participant's existing conventional hearing aids. Although equivalent outcomes have been shown for ''basic'' and ''advanced'' hearing aids (Cox et al, 2016;Johnson et al, 2016), this finding likely arose because the made-for-smartphone hearing aids trialed could have been a much higher specification than participant's existing hearing aids. For the other smartphone-connected listening devices, participants expressed ambivalence concerning perceived sound quality.…”
Section: Opportunitymentioning
confidence: 93%
“…Johnson and colleagues 11 found that only 10 studies were available in the peer-reviewed literature that had reported HA outcomes for patients with MSNHL, and most of those investigations only involved low levels of evidence, were rather dated, and reported findings for analog and early digital devices. Cox et al and Johnson et al, [21][22][23] however, reported outcomes from studies that compared entry-to premium-level ADT HAs for patients with mild and moderate SNHL. Although the findings for persons with MSNHL were similar to those with moderate losses, outcomes were not reported separately for the group with MSNHL.…”
Section: Abstract: Mild Hearing Loss Adults Advanced Digital Hearinmentioning
confidence: 99%